# 8x+9y=-1 x=6-2ySolve the system by using the substitution method.

*print*Print*list*Cite

### 3 Answers

Given the equations:

8x+9y = -1...........(1)

x = 6 - 2y ...............(2)

we need solve for x and y.

We will use the substitution method to solve.

We will substitute (2) into (1).

==> 8x+9y = -1

==> 8(6-2y) + 9y = -1

==> 48 - 16y + 9y = -1

==> -7y = -49

Now we will divide by -7

==> y= -49/-7 = 7

==> y= 7

==> x = 6-2y = 6-2(7) = 6 -14 = -8

Then the solution for the system is:

**x = -8 and y= 7**

8x+9y=-1 & x=6-2y

8(6-2y) + 9y = -1

48-16y+9y = -1

48-7y = -1

48+1 = 7y

49=7y

y=7

To solve 8x+9y=-1....(1) and x=6-2y...(2).

We have 8x = -1-9y.

So x = -(1+9y)/8. We substitute x = -(1+9y)/8 in (2):

-(1+9y)/8 = 6-2y. We multiply by 8:

-1-9y = 8(6-2y) = 48-16y.

We add 16y +1 to both sides:

-9y+16y = 48+1= 49.

7y = 49

7y/7 = 49/7 = 7.

y = 7.

We put y= 7 in equation (2):

x= 6-2y = 6-2*7 = -8.

So x= -8 and y = 7.